Chapter 13 Reflective Practice Professional Learning for Faculty at an EMI Institution in the UAE - Gitsaki, Christina (Taylor & Francis, 2023)
A key element in bringing long-term change in teacher practice is engaging teachers in reflection. While being a reflective practitioner is an important part of being an educator, using systematic reflection to help improve teaching practice requires training and mentorship. This chapter describes a professional development programme that utilised the Scholarship of Teaching and Learning framework in an English as a Medium of Instruction university in the United Arab Emirates. The programme aimed to raise awareness among faculty of the benefits of reflective practice and guide them through the process of designing their own classroom interventions to help measure the extent to which their teaching strategies and materials were effective in supporting students successfully attain their learning outcomes. Measures of impact are presented, while three case studies from faculty members who attended the Scholarship of Teaching and Learning programme are used to further illustrate the effect of the programme on teaching practice. The chapter concludes with tips on how to implement a Scholarship of Teaching and Learning programme to provide faulty in a multinational higher education institution with transformative professional development.